Novel variants of seryl-tRNA synthetase resulting in HUPRA syndrome featured in pulmonary hypertension - Yang, Fan; Wang, Dan; Zhang, Xuehua; Fan, Haoqin; Zheng, Yu; Xiao, Zhenghui; Chen, Zhi; Xiao, Yunbin; Liu, Qiming (Frontiers in Cardiovascular Medicine, 2023)
Hyperuricemia, pulmonary hypertension, and renal failure in infancy and alkalosis syndrome (HUPRA syndrome) is an ultrarare mitochondrial disease that is characterized by hyperuricemia, pulmonary hypertension, renal failure, and alkalosis. Seryl-tRNA synthetase 2 (SARS2) gene variants are believed to cause HUPRA syndrome, and these variants result in the loss of function of seryl-tRNA synthetase. Eventually, mutated seryl-tRNA synthetase is unable to catalyze tRNA synthesis and leads to the inhibition of the biosynthesis of mitochondrial proteins. This causes oxidative phosphorylation (OXPHOS) system impairments. To date, five mutation sites in the SARS2 gene have been identified. We used whole-exome sequencing and Sanger sequencing to find and validate a novel compound heterozygous variants of SARS2 [c.1205G>A (p.Arg402His) and c.680G>A (p.Arg227Gln)], and in silico analysis to analyze the structural change of the variants. We found that both variants were not sufficient to cause obvious structural damage but changed the intermolecular bond of the protein, which could be the cause of HUPRA syndrome in this case. We also performed the literature review and found this patient had significant pulmonary hypertension and minor renal dysfunction compared with other reported cases. This study inspired us to recognize HUPRA syndrome and broaden our knowledge of gene variation in PH.